myths And Their Representation In The Contemporary Algerian Novel - The Case Of "the Valley Of The Djine’s Novel” By Mabrouk Dridi- - boukhennouf, chahira (El Omda in Linguistics and Discourse Analysis, 2024)
Modern writers have adopted new insights into their literary writings, relying on intensification, suggestion and symbolism in their various poetic and prose texts. Perhaps among the popular genres they have adopted, we may find myths that are a folk literary genre, an artistic mask, bearing many intense symbols, and profound connotations; therefore, in their fiction work, the writers employed it to take advantage of its potential, fraught with multiple human and intellectual meanings. The Algerian novelist “ Mabrouk Dridi is one of the modern novelists who employ myths in fiction works, and this is evident in his novel entitled "The Valley of the Djine", trying to analyze old mythical texts and revive them in a novelist format in accordance with modern writing. His novel came to be rich in symbolic, artistic dimensions and dense connotation.